2021
DOI: 10.1038/s41598-021-96093-1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic, structural, and proteomic changes in Candida albicans cells induced by the protein-carbohydrate fraction of Dendrobaena veneta coelomic fluid

Abstract: The isolated protein-polysaccharide fraction (AAF) from the coelomic fluid of Dendrobaena veneta earthworm shows effective activity against Candida albicans yeast. Fungal cells of the clinical strain after incubation with the active fraction were characterized by disturbed cell division and different morphological forms due to the inability to separate the cells from each other. Staining of the cells with acridine orange revealed a change in the pH of the AAF-treated cells. It was observed that, after the AAF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 105 publications
(117 reference statements)
1
19
0
Order By: Relevance
“…Previous chemical analyses carried out in studies on antifungal activity 27 , 28 , 30 showed that proteins of the lysenin family: lysenin-related protein 2 (LRP2) and lysenin, which were identified with an accuracy of 95% and 90% sequence coverage, respectively, were the main components of Venetin-1. Lysenin is a 33 kDa protein found in the coelomic fluid of earthworms 50 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous chemical analyses carried out in studies on antifungal activity 27 , 28 , 30 showed that proteins of the lysenin family: lysenin-related protein 2 (LRP2) and lysenin, which were identified with an accuracy of 95% and 90% sequence coverage, respectively, were the main components of Venetin-1. Lysenin is a 33 kDa protein found in the coelomic fluid of earthworms 50 .…”
Section: Discussionmentioning
confidence: 99%
“…The system was controlled by SageElf software version 1.08. It yielded 12 fractions of the preparation, which were then digested using a standard FASP procedure and trypsin (Trypsin Gold, Promega) 27 , 65 . Fractions obtained from two runs were combined for one FASP procedure.…”
Section: Methodsmentioning
confidence: 99%
“…2 µL of the cell suspension was analyzed under the microscope. The dyes were used for visualization of genetic material of the cells in their current state: regular cells showed blue fluorescence of nuclei, apoptotic cells exhibited bright white florescence of fragmented genetic material, and necrotic cells had red fluorescence 39 , 40 .…”
Section: Methodsmentioning
confidence: 99%
“…Next, the cells were transferred into a sublimation chamber with a temperature of − 92 °C for 12 min. After that, the frozen cultures were cut in the preparation chamber and analyzed with a ZEISS Ultra Plus Field Emission Microscope (Carl Zeiss, Germany) with electron high tension (EHT) 5 kV and under magnification 30.000 × 39 , 42 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation